Características anatómicas de la madera de cinco especies del estado de Jalisco, México - Perez Olvera, Carmen de la Paz; Quintanar Isaias, Alejandra (Instituto de Ecología, A.C., 1994)
Macroscopic and microscopic features of the wood anatomy of Alnus jorullensis Kunth, Clethra mexicana DC., Quercus candicans Née, Quercus castanea Née and Tilia mexicana Schlecht. collected in the state of Jalisco are given. Distinctive anatomical features of each are rebounded, and results are compared with those from other individuals studied in different sites. Differences in esthetic features, cell elements sizes, in porosity and abundance of ergastic contents were observed.